2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6654874
|View full text |Cite
|
Sign up to set email alerts
|

ccnSim: An highly scalable CCN simulator

Abstract: Abstract-Research interest about Information Centric Networking (ICN) has grown at a very fast pace over the last few years, especially after the 2009 seminal paper of Van Jacobson et al. describing a Content Centric Network (CCN) architecture. While significant research effort has been produced in terms of architectures, algorithms, and models, the scientific community currently lacks common tools and scenarios to allow a fair crosscomparison among the different proposals.The situation is particularly complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 12 publications
(16 reference statements)
0
35
0
Order By: Relevance
“…ICN evaluation: There are many ICN evaluation platforms such as ndnSIM [10], ccnSim [20], DEC [5], and Mini-CCNx [15]. Unfortunately, our experiences showed that these cannot handle the scale of the workload and the topology we study in this paper.…”
Section: Icn Visionmentioning
confidence: 92%
See 1 more Smart Citation
“…ICN evaluation: There are many ICN evaluation platforms such as ndnSIM [10], ccnSim [20], DEC [5], and Mini-CCNx [15]. Unfortunately, our experiences showed that these cannot handle the scale of the workload and the topology we study in this paper.…”
Section: Icn Visionmentioning
confidence: 92%
“…There are several ICN simulation platforms currently in use including CCNx [1], ccnSim [20], DCE [5], mini-CCNx [15], and ndnSIM [10]. ndnSIM is generally considered to be the most scalable ICN platform; e.g., as reported by Afsanyev [10] et al, CCNx, ccnSim, DCE, and mini-CCNx can only support ICN simulations with a few hundred routers, and cannot be used for our large-scale evaluation with 80,000+ routers.…”
Section: Need For a New Icn Simulation Platformmentioning
confidence: 99%
“…CCN/NDN has many simulators designed which could run a simulation environment for the basic CCN architecture. CCnx [32] , ndnSIM [33] , ccnSim [34] and OMNet++ [35] are the most common examples of CCN simulators. Most of these simulators are open source and is written in C++.…”
Section: Methodsmentioning
confidence: 99%
“…The FIB consists of the forwarding entries for the interfaces connected to the node and based on these FIB entries the interest is send to the next node. The forwarding strategies are based on the many forwarding architectures like multipath forwarding or shortest path forwarding or the random forwarding [34] . So, the interest moves on towards the producer until it finds the content either in the CS of the nodes or in the content producer.…”
Section: Ccn Architecture 한국시뮬레이션학회 논문지mentioning
confidence: 99%
“…In order to evaluate the accuracy of our proposal, we compared the analytical model presented in the previous section with the results of simulations under ccnSim [12], which is a discrete-event and a chunk-level simulator for CCN networks. The accuracy of MACS, compared to the simulation results, can be affected by many parameters.…”
Section: A Simulation Environmentmentioning
confidence: 99%